Tinjauan Yuridis Paradigma "Enam Agama Resmi" di Indonesia: Analisis Kritis dari Perspektif Hukum HAM Internasional - Ferco Arvian (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2026)
The paradigm of the "six official religions" in Indonesia is an administrative construction that has been rooted in the implementation of state policies since the New Order Era, even though Indonesia constitutionally guarantees religious plurality. This paper analyzes the compatibility of administrative restrictions on minority religions such as Baha'is, Jews, Sikhs, and Believers with international human rights protection standards, especially the International Covenant on Civil and Political Rights (ICCPR) which Indonesia has ratified through Law Number 12 of 2005. This study uses a normative juridical method with a comparative approach of international law. The results of the analysis show that although the term "six official religions" is not explicitly found in national laws and regulations, administrative practices that distinguish adherents of religions outside the six religions violate the principle of non-discrimination guaranteed in Article 18 of the ICCPR and Article 2 of the Universal Declaration of Human Rights (UDHR). The study's conclusions recommend a paradigm shift from a model of theological recognition toward inclusive protection of civil and political rights.